A grand materialism in the new art from China - Wiseman, Mary Bittner (Philosophy and cultural identity., 2020)
"Material matters in new Chinese art, which presents its subjects through the directness and immediacy of its material. This book applies theories by Osborne and Danto to new Chinese art to show how artists are working below the level of language to make each work of art prove that it is art"--